Fabrication, Characterization, and Antimicrobial Activity, Evaluation of Low Silver Concentrations in Silver-Doped Hydroxyapatite Nanoparticles. (26th May 2013) - Costescu, A.; Ciobanu, C. S.; Iconaru, S. L.; Ghita, R. V.; Chifiriuc, C. M.; Marutescu, L. G.; Predoi, D.
Abstract : The aim of this study was the evaluation of ( Ca 10 - x Ag x ) ( PO 4 ) 6 ( OH ) 2 nanoparticles (Ag:HAp-NPs) for their antibacterial and antifungal activity. Resistance to antimicrobial agents by pathogenic bacteria has emerged in the recent years as a major public health problem worldwide. In this paper, we report a comparison of the antimicrobial activity of low concentrations silver-doped hydroxyapatite nanoparticles. The silver-doped nanocrystalline hydroxyapatite powder was synthesized at 100°C in deionised water. The as-prepared Ag:Hap nanoparticles were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), FT-IR, and FT-Raman spectroscopy. X-ray diffraction (XRD) studies demonstrate that powders obtained by coprecipitation at 100°C exhibit the apatite characteristics with good crystal structure, without any new phase or impurities found. FT-IR and FT-Raman spectroscopy revealed the presence of the various vibrational modes corresponding to phosphates and hydroxyl groups and the absence of any band characteristic to silver. The specific microbiological assays demonstrated that Ag:HAp-NPs exhibited antimicrobial features, but interacted differently with the Gram-positive, Gram-negative bacterial and fungal tested strains.